Development of Eco-Friendly Binders for Silicon Anodes in All-Solid-State Batteries Under Low Operating Pressure - Jun, Seunggoo; Lim, Haechannara; Song, Yongbae; Jung, Yoon Seok (Meeting abstracts (Electrochemical Society), 2024)
The growing demand for vehicle electrification and sophisticated energy storage systems is driving research into lithium-ion batteries (LIBs) with high energy density. Employing inorganic materials as solid electrolytes (SEs) presents a compelling strategy to enhance the energy density and safety profile of these batteries. Nonetheless, the integration of Li metal anodes (LMAs) in all-solid-state batteries (ASSBs) still presents dendrite issues, and without specific protective layers like C-Ag, cycle stability remains a challenge. In contrast, Si anodes, which are not subject to these limitations, may offer a viable alternative. However, Si anodes in LIBs are prone to extreme volume expansion (> 300%) during charge-discharge cycles, causing fractures and loss of electrical contact. Si ASSBs can have electrodes in the form of pure Si and a composite with the SEs. Recent studies suggest that each exhibits different failure mechanisms. Specifically, in the case of pure Si, numerous vertical cracks in the electrode and delamination with SE layer have been reported. In low-operating pressure, the resistance to electronic conduction in Si anode is further exacerbated. ASSBs present significant environmental concerns related to their manufacturing and recycling processes, which frequently incorporate hazardous substances such as NMP solvent and fluorinated polymers, including PVDF and PTFE. To commercialize ASSBs, two issues must be resolved. In our study, we designed an aqueous-process-based binder for eco-friendly strategies and utilized it for low pressure operating Si ASSBs. Additionally, the binder significantly contributes improving electrical conductivity during the delithiation process with adhesion properties, as observed by an electrical conductivity measurement cell. The NCM/Si full cell exhibited high discharge capacity at 30°C and 5 MPa with high rates. Our design demonstrates enhanced performance of ASSBs under reduced pressure conditions, addressing a critical aspect of practical applicability. [1] H. S. Tan Darren et al., Science 2021, 373, 1494. [2] H. Huo et al., Nat. Mater. 2024, 23, 543.